Toxic effects of the herbicide 2,4-dichlorophenoxyacetic acid on lymphoid organs of the rat - Kaioumova, Dinara; Kaioumov, Farit; Opelz, Gerhard; Süsal, Caner (Chemosphere, 2001)
We investigated the toxicity of the widely used herbicide dimethylammonium salt of 2,4-dichlorophenoxyacetic acid (DMA-2,4-D) on the lymphoid system of rats after a single dose oral administration using histological, cytochemical and molecular methods. DMA-2,4-D destroyed in a dose- and time-dependent manner the vascular integrity of the thymus and caused cell depletion in the white pulp of the spleen and in the cortex of the thymus, which was at least partly due to programmed cell death. DMA-2,4-D appeared to have hemolytic activity and caused intravascular hemolysis of erythrocytes. An increased hemosiderin content in macrophages of the spleen indicated phagocytosis of lysed erythrocytes. We conclude that acute DMA-2,4-D herbicide poisoning results in severe damage of the lymphatic organs thymus and spleen.
Available online: 30 April 2001
Gesehen am 08.03.2021